Hubungan Pertambahan Berat Badan Ibu Hamil dengan Berat di RSIA Sitti Khadijah Makassar - Khomeny, Imran Al Mu’min; Vitayani, Sri; Aulia, Nur; Nurmadilla, Nesyana; Darma, Sidrah (Faculty of Medicine, 2025)
Pregnancy involves physical, psychological, and social aspects, with maternal weight gain being an important indicator for assessing maternal health and fetal development. This study aims to analyze the relationship between maternal weight gain during pregnancy and birth weight of infants born at Sitti Khadijah 1 Muhammadiyah Mother and Child Hospital in Makassar. An analytical observational study with a cross-sectional design was conducted, involving 40 pregnant women who gave birth between January and February 2025. Data were collected through medical records and the Mother and Child Health Book, then analyzed using the Chi-square test. The results showed that most mothers experienced weight gain within the normal category (70.7%), and 95% of babies were born with normal birth weight. There was a significant association between maternal weight gain and birth weight, with a p-value of 0.042. The study concluded that normal or higher maternal weight gain is associated with a higher likelihood of giving birth to infants with normal birth weight. This study emphasizes the importance of monitoring maternal weight gain to prevent low birth weight.